Berkebun di Rumah pada Masa Pandemi dengan Memanfaatkan Sampah Rumah Tangga - Sartono Joko Santosa; Siswadi Siswadi; Andi Fajarwanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Food is a basic need for humans that must be fulfilled as a basic need; food has an essential meaning and role in a nation's life. The problems faced during the Covid 19 pandemic have forced everyone to keep quiet and work from home so that everyone tries to take advantage of this free time with productive activities. One of these activities is gardening at home using household waste. To make this happen, from April to September 2020, the community service team conducted counseling and training and practices for the Amuktiwo Ngubo farmer group, Kestalan sub-district, Banjasari District, Surakarta City, Central Java. The results of the program show that the Covid 19 pandemic forces every citizen, especially partner groups, to do activities at home, which results in a lot of free time available, so gardening at home by using household waste as a planting medium is the most appropriate solution because the environment is clean and healthy. The crop yields can meet the needs of the kitchen, which results in reduced expenses. Also, if this program is implemented nationally, the goal of community food security will be achieved.